Clinical N3 is an independent risk factor of recurrence for breast cancer patients achieving pathological complete response and near-pathological complete response after neoadjuvant chemotherapy - Qian, Xiaoyan; Xiu, Meng; Li, Qing; Wang, Jiayu; Fan, Ying; Luo, Yang; Cai, Ruigang; Li, Qiao; Chen, Shanshan; Yuan, Peng; Ma, Fei; Xu, Binghe; et al. (Frontiers in Oncology, 2022)
Background: Although achieving pathological complete response (pCR) and near-pathological complete response (near-pCR) after neoadjuvant chemotherapy (NAC) in breast cancer predicts a better outcome, some patients still experience recurrence. The aim of our study was to investigate the predictive factors of recurrence in the pCR and near-pCR population. Methods: We reviewed 1209 breast cancer patients treated with NAC between January 2010 and April 2021 in the Cancer Hospital, Chinese Academy of Medical Sciences (CHCAMS). A total of 292 patients achieving pCR and near-pCR were included in our analysis. pCR was defined as ypT0N0/ypTisN0. Near-pCR was defined as ypT1mi/1a/1bN0 or ypT0/isN1mi. Clinical features, and follow-up information were collected. Survival and predictive factors of recurrence were analyzed. Results: Of the 292 patients, 173 were pCR and 119 were near-pCR. The median age was 46 years (range 23-75 years). The predominant tumor subtypes were human epidermal growth factor receptor type 2 (HER2) positive breast cancer (49.0%) and triple-negative breast cancer (TNBC) (30.8%). The median duration of follow-up was 53 months (range 9-138 months). A total of 25 (8.6%) patients developed recurrence, with 9 (5.2%) in the pCR group and 16 (13.4%) in the near-pCR group. The vast majority of recurrence occurred within 36 months from onset of NAC. The 5-year recurrence-free survival (RFS) rate of patients achieving pCR was significantly higher than that of patients achieving near-pCR (94.6% vs.85.6%, P=0.008). But the 5-year overall survival (OS) rate between the two cohorts had no statistical difference (94.3% vs. 89.6%, P=0.304). Clinical N3 (cN3) before NAC was an independent risk factor of recurrence in patients who achieved pCR (P=0.003) and near-pCR (P=0.036). Tumor size before NAC, subtypes of breast cancer and chemotherapy regimens showed no significant association with RFS both for patients who achieved pCR and near-pCR (P>0.05). Conclusions: cN3 before NAC was an independent risk factor of recurrence in patients who achieved pCR and near-pCR. It is worthwhile to monitor closely for patients with cN3, especially in the first 3 years.